Evaluation of green space systems in small towns of Kyiv region - Yukhnovskyi Vasyl Yu. (Sciendo, 2021)
We analysed the current state of greening of small towns in the Kyiv region; small towns constitute 80% of all towns and cities in the region. A difference is shown to exist between the classification of green plantings that is used in Ukraine and the world-wide approach of green infrastructure. This makes it incorrect to compare the indicators of landscaping of towns in Ukraine against those of other countries. Based on the data of Master Plans of towns, the generally accepted indicators of landscaping of urban areas were calculated: provision of greenery per capita and level of landscaping. These indicators of landscaping for small towns were analysed according to different approaches. It is found that, according to the traditional calculation, the provision of green plantations exceeds 300 m2 per capita for only 5% of small towns of the region, but for 70% according to the approach of green infrastructure. The provision of green areas for public use meets the established state standards (8–11 m2 per capita) for only 35% of small towns in the region. Small towns are grouped into four clusters according to the similarity of landscaping indicators, where only the difference in the availability of green plantings of public use was unreliable among the clusters.